Teachers' beliefs about the trends of current physical education - Nampai, Udon; Setiawan, Caly; Yeats, Jeremy T. (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2022)
This study aimed to investigate the beliefs among professionals in the field of physical education at the elementary level, more specifically in the context of Thailand. The participants were five exemplary elementary physical education (PE) teachers. All participants signed informed consent prior to data collection. We used semi-structured interviews to gather information on participants' beliefs. Each interview lasted approximately 45 minutes. All interviews were audio recorded and later transcribed for analysis. Data collection occurred in two ways: (1) in-depth semi-structured interviews and (2) semi-structured follow-up interviews. Data were analyzed using a thematic coding procedure to find the significant statements related to research questions. Results showed three themes constructed from data analysis, including trends: (1) to teach the foundation of basic skills that moved beyond sport-oriented PE, (2) to consider physical education for Health and integrated physical education, and (3) to perceive limited time to deliver contemporary physical education. We conclude that the beliefs about the trends in physical education have been aligned with the global trends in physical education. These cover topic areas of skill development and health issues with a strong emphasis on physical education that serves the best interests of the children. Relevant stakeholders should then ensure that physical education will be delivered according to the interest of today's children. Future research should seriously focus on this specific area of study, encompassing policy, program, and practice of physical education.